A Simulink/Simscape dynamic modelling study on shifting the power output profile of a direct steam generation solar power system with steam/water storage - Ehtiwesh, Amin (2023)
Solar thermal power plants convert thermal energy from direct solar radiation into mechanical work and electricity via a thermodynamic cycle. This method produces renewable electricity. A direct steam generation technology (DSG), which generates steam directly in the solar field's absorber tubes and feeds it directly to the turbine or thermal storage, is one of the many options in solar thermal power plants. It has a number of intriguing advantages and is a promising technology. However, one of the major problems with the use of the direct steam generation technology is that it is affected by the fluctuation of solar radiation, which results in the production of fluctuating power output and no economic competition for long-term storage. The design of the control system is complicated by the steam generation system's challenging dynamic behaviour. It is primarily caused by the coexistence of two-phase flow in the absorber tubes and the natural transitory feature of solar radiation. In solar thermal power plants, thermal storage is a critical requirement. There are different types of heat storage systems in solar plants such as molten salts, concretes, phase change materials and steam accumulators. The steam accumulator has been adopted in Planta Solar 10 project. Steam accumulator is a viable option for decreasing the influence of changing irradiance on the power generation of solar thermal systems since they have fast reaction time and high discharge rates due to the rapid evaporation and condensation of water/steam under non-equilibrium conditions. This thesis aims to study the dynamic behaviour of a novel direct steam generation solar power system integrated with a steam/water accumulator for shifting its power output profile to match the electricity demand profile in a Libyan hospital as a case study. Another issue in DSG solar power systems is that expansion in turbine might happen in liquid-vapour two-phase region. Use of a cascade Rankine cycle can be a solution, in which an organic Rankine cycle (ORC) is a bottom cycle, while a steam Rankine cycle is a top cycle with a higher condensation temperature to mitigate the issue of wet expansion. The bottom cycle can also run separately using low-temperature residue steam/water in the accumulator to offer a further capacity in shifting power output profile. Therefore, the design of a cascade steam-organic Rankine cycle integrated with steam\water accumulator is studied from operating and thermodynamic perspectives, aiming to fully unlock the potential of such advanced high-efficiency cogeneration systems. This thesis presents a comprehensive literature review on Rankine cycle solar power generation systems regarding cycle configurations, thermal storage and working fluids. The design, validation and parametric study of a direct steam generation solar power system is conducted for Libyan climate conditions, particular with dynamic simulation of a steam/water accumulator. Moreover, a cascade steam-organic Rankine cycle solar power system integrated a steam accumulator was studied. Finally, the cascade steam-organic Rankine cycle solar power system integrated with two water accumulators was modelled. All the designs presented in this thesis was simulated by using Simulink\Simscape software in order to see the dynamic behaviour of systems under different climate conditions. As a case study, the electricity demand profile of a Libyan hospital was chosen as a target in the design of system. The results demonstrated that by using 1544m2 of parabolic trough solar collectors and 160m3 of steam storage tank with a proper control of flow rate, the power output profile of the system can meet the electricity demand of the Libyan hospital even at night. In the cascade steam-organic Rankine cycle solar power system coupled with the steam accumulator with and without using a recuperator, the findings reveal that the recuperative system outperforms the non-recuperative system in terms of power generation and thermal efficiency. In the cascade steam-organic Rankine cycle solar power system integrated with two water storage tanks, results show that the top cycle output is higher than ORC power output in the nominal operation mode. At the peak radiation time, the top cycle generates 136 kW, while the ORC generates 37 kW. In the discharging mode in the evening, a separate operation the bottom ORC system can still generate 31 kW for six hours based with using a 51 m3 hot water tank.